Wayback machine: reincarnation to vanished online citations. Issue 2 (7th April 2015) - Kumar, B T Sampath; Vinay Kumar, D; Prithviraj, K.R.
Abstract : Purpose: – The purpose of this paper is to know the rate of loss of online citations used as references in scholarly journals. It also indented to recover the vanished online citations using Wayback Machine and also to calculate the half-life period of online citations. Design/methodology/approach: – The study selected three journals published by Emerald publication. All 389 articles published in these three scholarly journals were selected. A total of 15, 211 citations were extracted of which 13, 281 were print citations and only 1, 930 were online citations. The online citations so extracted were then tested to determine whether they were active or missing on the Web. W3C Link Checker was used to check the existence of online citations. The online citations which got HTTP error message while testing for its accessibility were then entered in to the search box of the Wayback Machine to recover vanished online citations. Findings: – Study found that only 12.69 percent (1, 930 out of 15, 211) citations were online citations and the percentage of online citations varied from a low of 9.41 in the year 2011 to high of 17.52 in the year 2009. Another notable finding of the research was that 30.98 percent of online citations were not accessible (vanished) and remaining 69.02 percent of online citations were still accessible (active). The HTTP 404 error message – "page not found" was the overwhelming message encountered and represented 62.98 percent of all HTTP error message. It was found that the Wayback Machine had archived only 48.33 percent of the vanished web pages, leaving 51.67 percent still unavailable. The half-life of online citations was increased from 5.40 years to 11.73 years after recovering the vanished online citations. Originality/value: – This is a systematic and in-depth study on recovery of vanished online citations cited in journals articles spanning a period of five years. The findings of the study will be helpful to researchers, authors, publishers, and editorial staff to recover vanishing online citations using Wayback Machine.